Research into Open Access: Impact and User Perspective - Heriyanto Heriyanto (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The title of this article is Research into Open Access: Impact and User Perspective. It aims to explore recent research into Open Access. This research was collected research about open access, analyzed them, dan summarised the pattern of the Open Access research conducted There is a growing body of research exploring open access. This research has focussed on two main areas of inquiry: impact and user perspective. Research exploring open access from the perspective of impact has investigated how frequently articles published in open access channels are cited compared to articles published in other channels. Research exploring open access from the perspective of user engagement has tried to fill this gap. For example, studies have explored how research students are aware of and use their university repository. It is expected that the result of this research can provide a guide for the future direction of Open Access research.